2019
DOI: 10.1186/s12889-019-6753-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of disease screening on awareness and management of hypertension and diabetes between 2011 and 2015: results from the China health and retirement longitudinal study

Abstract: Background There has been a limited recognition of hypertension and diabetes in China which has compromised optimal treatment. It is not clear if a screening program implemented by a national health survey has improved awareness and management of these conditions. Methods The China Health and Retirement Longitudinal Study (CHARLS) is an ongoing longitudinal health survey conducted since 2011 among Chinese people aged 45 years and older. Participants have been assessed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 30 publications
5
30
0
Order By: Relevance
“…Several previous epidemiological studies have reported on the treatment of hypertension in Chinese elderly populations. 18 19 One of those studies, the China Health and Retirement Longitudinal Study, measured the treatment of hypertension in a nationally representative sample of 9357 Chinese aged 45 years or above, which provided the best comparison data for our study. 18 When compared with the findings from that study, the treatment of hypertension in this study indicated higher incidence, 51.0% vs 54.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous epidemiological studies have reported on the treatment of hypertension in Chinese elderly populations. 18 19 One of those studies, the China Health and Retirement Longitudinal Study, measured the treatment of hypertension in a nationally representative sample of 9357 Chinese aged 45 years or above, which provided the best comparison data for our study. 18 When compared with the findings from that study, the treatment of hypertension in this study indicated higher incidence, 51.0% vs 54.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 18 19 One of those studies, the China Health and Retirement Longitudinal Study, measured the treatment of hypertension in a nationally representative sample of 9357 Chinese aged 45 years or above, which provided the best comparison data for our study. 18 When compared with the findings from that study, the treatment of hypertension in this study indicated higher incidence, 51.0% vs 54.4%, respectively. 18 Other regional studies have also previously examined the treatment of hypertension in local elderly residents.…”
Section: Discussionmentioning
confidence: 99%
“…However, rural migrants are also constrained by many barriers when we have a close look. These barriers include lack of knowledge of NCMS, difficult reimbursement policies, and lack of health awareness [14][15] [16] [17]. Accordingly, an uncertainty of the direction of disparity distribution among NCMS beneficiaries was raised.…”
Section: Resultsmentioning
confidence: 99%
“…Patients who are judged to be diabetes and have no consciousness of illness are judged to be diabetes without consciousness of illness, a patient who is judged to be a diabetes with a illness consciousness is judged to be a patient with a illness consciousness diabetes. [9] The data screening process is shown in Figure 1.…”
Section: Target Inclusion and Calculation Criteriamentioning
confidence: 99%